2019
DOI: 10.1007/s13595-019-0875-2
|View full text |Cite
|
Sign up to set email alerts
|

Polyculture affects biomass production of component species but not total standing biomass and soil carbon stocks in a temperate forest plantation

Abstract: & Key message Over-yielding of stand biomass did not occur in a tree polyculture comprised of Betula pendula, Alnus glutinosa and Fagus sylvatica selected for contrasting traits. This was due to antagonistic interactions between the component species. Fine root dynamics and soil C stocks were unaffected by species mixture. & Context Increasing CO 2 fixation in tree biomass through afforestation and forest management actions has potential for costeffective climate mitigation. The influences of tree mixture on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…Alder is a fast-growing, light-demanding species, which in this study grew faster neighboring Douglas fir. This trend is similar to that observed by Ahmed et al (2019) who showed that in a three-species polyculture comprised of Alnus glutinosa, Betula pendula and Fagus sylvatica the biomass of alder was greater in mixture than in monoculture after 6 years of growth. While no above-ground overyielding was observed in their study, this was explained by the suppression of the slow-growing Fagus sylvatica in mixture.…”
Section: Tree Traits That Relate To Soil Functionsupporting
confidence: 90%
“…Alder is a fast-growing, light-demanding species, which in this study grew faster neighboring Douglas fir. This trend is similar to that observed by Ahmed et al (2019) who showed that in a three-species polyculture comprised of Alnus glutinosa, Betula pendula and Fagus sylvatica the biomass of alder was greater in mixture than in monoculture after 6 years of growth. While no above-ground overyielding was observed in their study, this was explained by the suppression of the slow-growing Fagus sylvatica in mixture.…”
Section: Tree Traits That Relate To Soil Functionsupporting
confidence: 90%
“…The higher soil carbon stock in the topsoil may be related with the accumulation of vegetal residue, the amount of organic matter, the root activity, and the microorganism's activity (Lal 2005;Babujia et al 2010;Dawud et al 2016;Ahmed et al 2019). This result agrees with that observed by Lima (2004), who reported the highest carbon content in the 0-5-cm layer in Eucalyptus forest compared with pasture, mostly justified by the presence of forest litter and microorganism's activity.…”
Section: Soil Carbon Stocks and Partitioning (Biomass + Soil) In Forest Plantationssupporting
confidence: 86%